Environmental impacts and benefits of organic Rankine cycle power generation technology and wood pellet fuel exemplified by electric arc furnace steel industry. (1st December 2016) - Lin, Yi-Pin; Wang, Wen-Hsian; Pan, Shu-Yuan; Ho, Chang-Ching; Hou, Chin-Jen; Chiang, Pen-Chi
Highlights: Application of ORC and wood pellet fuel in an EAF was evaluated by real plant data. Environmental impacts and benefits were quantified using a cradle-to-gate approach. Benefit cost ratio of ORC and wood pellet were determined by cost benefit analysis. Environmental benefits from wood pellet fuel were higher than ORC power generation. ORC exhibited superior potentials on the capital and O&M costs to wood pellet fuel. Abstract: Iron- and steel-mill manufacturing are the material- and energy-intensive industries in the world, accounting for 22% of total industrial energy use in 2011; thereby leading to significant carbon dioxide (CO2 ) emissions. In this study, the environmental impacts and benefits for the applications of organic Rankine cycle (ORC) power generation and wood pellet fuel in the electric arc furnace (EAF) steel industry were evaluated using a cradle-to-gate life-cycle approach. The business-as-usual scenario of the EAF manufacturing was first established, and then compared with the scenarios of ORC facility and wood pellet fuel. The system boundary of heavy fuel oil production includes resource extraction, refining and processing, and transportation. The inventory data used in life cycle assessment were gathered from the information of real plant operation. The results indicated that both the ORC facility and replacement of heavy fuel oil by wood pellet fuel can mitigate the environmental impacts on ecosystems, human health and resource depletion. The environmental benefits of integrating the ORC power generation in an EAF steelmaking plant were less than those of applying wood pellet fuel for reheating furnace. However, the benefit-cost ratio of ORC process was greater than that of wood pellet fuel because the capital, and operation and maintenance costs of ORC process were lower than that of wood pellet fuel process.